The Unfolding Model of Voluntary Turnover: A Replication and Extension - Lee, Thomas; Mitchell, Terence R.; Holtom, Brooks C.; McDaneil, Linda S.; Hill, John W. (Academy of Management Journal, 1999)
This work reports further theoretical development of Lee and Mitchell's (1994) unfolding model of voluntary turnover, which describes different psychological paths that people take when quitting organizations. Ambiguities in the model were identified, and hypotheses aimed at resolving these ambiguities were tested on a sample of 229 former employees from the ?Big 6? public accounting firms. The results provide a theoretical and quantitative extension of an earlier qualitative assessment of the unfolding model. Implications are discussed.